Stalking, threatening and attacking public figures: a psychological and behavioral analysis - Meloy, J. Reid (Oxford University Press, 2008)
Public figure stalking : the state of the science / J. Reid Meloy, Lorraine Sheridan, Jens Hoffmann -- A forensic investigation of those who stalk celebrities / J. Reid Meloy, Kris Mohandie, Mila Green McGowan -- The role of psychotic illness in attacks on public figures / Paul E. Mullen ... [et al.] -- Homicidal celebrity stalkers : dangerous obsessions with nonpolitical public figures / Louis B. Schlesinger, V. Blair Mesa -- On public figure howlers / Frederick S. Calhoun, Stephen W. Weston -- Stalking, threatening, and attacking corporate figures / Jens Hoffmann, Lorraine Aheridan -- The public figure assassin as terrorist / James Biesterfeld, J. Reid Meloy -- Contributions from attachment theory and psychoanalysis to advance understanding of public figure stalking and attacking / Jens Hoffmann, J. Reid Meloy -- Celebrities as victims of stalking / Jens Hoffmann, Lorraine Sheridan -- Psychopathy and predatory stalking of public figures / Mary Ellen O'Toole, Sharon S. Smith, Robert D. Hare -- Two case studies of corporate-celebrity victims : the stalking of Steven Spielberg and Stephen Wynn / J. Reid Meloy, Kris Mohandie -- Toward the measurement and profiling of celebrity worship / John Maltby, David Giles -- Fanning the flames of fandom : celebrity worship, parasocial interaction, and stalking / Brian H. Spitzberg, William R. Cupach -- Operations of the LAPD threat management unit / Jeff Dunn -- Risk assessment of public figure stalkers / P. Randall Kropp, Stephen D. Hart, David R. Lyon -- Preventing assassination : psychiatric consultation to the United States Secret Service / Robert T.M. Phillips -- Offender profiling and celebrity stalking cases / Karl Roberts -- Prosecuting celebrity stalkers / Rhonda Saunders, Sean Wainwright -- Use of threat assessment for the protection of the United States Congress / Mario J. Scalora, William Zimmerman, David G. Wells -- From violent words to violent deeds : assessing risk from FBI threatening communication cases / Sharon S. Smith